Correcting bias in rainfall inputs to a semi-distributed hydrological model using downstream flow simulation errors. Issue 15 (18th November 2017) - Hughes, D.A.; Gray, R.
ABSTRACT: The focus of this study is on bias correcting semi-distributed rainfall inputs into a hydrological model applied in the Okavango River basin in southern Africa, where there are very few local observations and heavy reliance is placed on global rainfall datasets. While the hydrological model, before rainfall bias correction, is able to represent the broad characteristics of the sub-basin streamflow responses, as demonstrated by good agreement between observed and simulated flow duration curves, there are many years where the annual volumes are over- or underestimated. The long records of observed flow at downstream stations are successfully used to bias correct the rainfall inputs to the upstream sub-basins using an analysis of their individual contributions to downstream flow and their annual rainfall–runoff response ratios. The results show improved simulations for the relatively shorter observation periods at the upstream gauging stations.